Peran pendidikan kewarganegaraan dalam pembentukan identitas nasional - zahra, fany fadhilatuz (Maliki Interdisciplinary Journal, 2025)
Civic education plays an important role as a medium that strengthens national identity. Civic education conveys the values ​​of Pancasila and strengthens civic education plays an important role in the formation of Indonesian national identity. In addition, civic education strengthens nationality and a sense of unity amidst cultural and ethnic diversity, and teaches them about their rights and obligations as citizens. Civic education also plays a role in the fight against extremism and separatism by communicating the values ​​of tolerance and unity. This learning helps to value local culture, develop excellent character and morality, and actively participate in social and national life. Support from the curriculum and excellent synergy from the school environment, family and community are essential for effectiveness. With educational learning everywhere, understanding civic education to strengthen our national identity will deepen us.